From sick role to narrative subject: An analytic memoir. (January 2016) - Frank, Arthur W
Questions of illness experience and identity are discussed, based on the analysis of a story told by the breast-cancer activist Audre Lorde. Displacing Parsons' conceptualization of illness as a sick role, I understand the ill person as a narrative subject, defined by discursive possibilities. Three discourses of illness are proposed: the medical institutional discourse, the discourse of illness experience, and the pink-ribbon discourse. Each has its preferred narratives. These discourses overlap and mutually affect each other. Problems with the Foucauldian conceptualization of the subject are considered, and a dialogical imagination of relations of governmentality is proposed.